2018
DOI: 10.1186/s13011-018-0177-y
|View full text |Cite
|
Sign up to set email alerts
|

Comorbid opioid use is undertreated among forensic patients with schizophrenia

Abstract: BackgroundSubstance use disorders are associated with poorer clinical outcomes in patients with schizophrenia. There is no specific treatment for amphetamine or cannabis use disorder, but methadone and buprenorphine are used as replacement therapy in the treatment of opioid dependence. Our aim was to study whether patients with schizophrenia have received opioid replacement therapy for their opioid use disorder.MethodsThe study sample consisted of 148 individuals diagnosed with schizophrenia who were in involu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“… 11 This may reflect a lack of willingness to participate in the study, inability to provide informed consent, or perhaps, undertreatment of OUD in patients with psychotic disorders. 42 The small number of participants in the psychotic disorder group also limited the statistical power available to detect group differences. Larger studies will be required in the future.…”
Section: Discussionmentioning
confidence: 99%
“… 11 This may reflect a lack of willingness to participate in the study, inability to provide informed consent, or perhaps, undertreatment of OUD in patients with psychotic disorders. 42 The small number of participants in the psychotic disorder group also limited the statistical power available to detect group differences. Larger studies will be required in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the complexity, it is well known that OMT (using well-tested opioid agonists of defined quality, dosage, release form, effects) reduces the harm related to OUD in comparison with ongoing use of illicit drugs outside of treatment. 55 …”
Section: Methods and Analysismentioning
confidence: 99%
“…Despite the complexity, it is well known that OMT (using well-tested opioid agonists of defined quality, dosage, release form, effects) reduces the harm related to OUD in comparison with ongoing use of illicit drugs outside of treatment. 55 In conclusion, we present a comparative international project initiative to study OMT in the Czech Republic, Norway and Denmark. Investigations will improve our knowledge of how national treatment systems evolve over time regarding patient flow and OMT participation and outcomes.…”
Section: Implications For Interventions and Future Policymentioning
confidence: 99%
“…Several epidemiologic studies have shown that schizophrenia spectrum disorders (SSDs) contribute significantly to years lived with disability [1]. Additionally, substance use disorders (SUDs) have been reported to co-occur commonly among patients with SSD (a comorbidity also known as dual diagnosis), attracting notable attention over the past few decades [2][3][4][5]. For example, in one epidemiological study, 47% of patients with schizophrenia were reported to have a SUD [2].…”
Section: Introductionmentioning
confidence: 99%
“…Most patients with comorbid SSD and substance use are Substance Use Patterns in Patients With SSD J Clin Med Res. 2020;12 (12):803-808 young males and have been shown to have a higher risk for medication noncompliance, multiple hospitalizations, unstable housing and homelessness, human immunodeficiency virus (HIV) infection, suicide, and violent behavior [3]. Regarding specific substances, those who use alcohol are reported to have higher hospital admissions, higher severity of positive symptoms, higher rates of extrapyramidal side effects including tardive dyskinesia, and "relative neuroleptic refractoriness" [2].…”
Section: Introductionmentioning
confidence: 99%